Strategi Kewirausahaan Berbasis Akuntansi untuk Meningkatkan Profitabilitas Usaha Kecil - Pranandha Ika Aprilia; Gita Purnama Sari; Liinaa Nurfatin Shafiyyah; Ari Anggraini Winadi Prasetyoning Tyas (Ikatan Da'i Indonesia, 2025)
In the era of globalization and increasingly fierce business competition, small businesses play a crucial role in driving economic growth, creating jobs, and improving public welfare. However, many small businesses face challenges in financial management due to simple record-keeping systems that do not comply with accounting standards. This article discusses the importance of accounting-based entrepreneurial strategies as a solution to increase small business profitability. Through the implementation of sound accounting, businesses can manage their finances in a more structured manner, monitor cash flow, determine competitive selling prices, and increase access to financing. This strategy also improves operational efficiency, transparency, and accountability, thereby strengthening competitiveness in the marketplace. Therefore, implementing accounting-based entrepreneurial strategies is a strategic step towards achieving the sustainability and growth of small businesses.